Distinguishing globally-driven changes from regional- and local-scale impacts: The case for long-term and broad-scale studies of recovery from pollution. Issue 2 (30th November 2017) - Hawkins, S.J.; Evans, A.J.; Mieszkowska, N.; Adams, L.C.; Bray, S.; Burrows, M.T.; Firth, L.B.; Genner, M.J.; Leung, K.M.Y.; Moore, P.J.; Pack, K.; Schuster, H.; et al.
Abstract: Marine ecosystems are subject to anthropogenic change at global, regional and local scales. Global drivers interact with regional- and local-scale impacts of both a chronic and acute nature. Natural fluctuations and those driven by climate change need to be understood to diagnose local- and regional-scale impacts, and to inform assessments of recovery. Three case studies are used to illustrate the need for long-term studies: (i) separation of the influence of fishing pressure from climate change on bottom fish in the English Channel; (ii) recovery of rocky shore assemblages from the Torrey Canyon oil spill in the southwest of England; (iii) interaction of climate change and chronic Tributyltin pollution affecting recovery of rocky shore populations following the Torrey Canyon oil spill. We emphasize that "baselines" or "reference states" are better viewed as envelopes that are dependent on the time window of observation. Recommendations are made for adaptive management in a rapidly changing world.